Characterization of Intestinal Parasitosis in Pregant Women at Ram Janaki Hospital, Janakpurdham (Tribhuvan University Journal of Microbiology, 2020)
Objectives: The objective of this study was designed to focus the prevalence, detection and identification of intestinal parasites and its associated factors among pregnant women.Methods: Total 264 stool samples were collected in a labeled dry, clean disinfectant free wide mouthed plastic container during antenatal visits at Ram Janaki Hospital, Janakpurdham and were examined by macroscopically and microscopically. The detection and identification of protozoal cysts, oocysts, trophozoites and helminthic eggs or larva was done by wet preparation and formalether sedimentation concentration technique. The data was analysed using SPSS 20 version and Microsoft Excel 2007. A Chi-square test was performed to predict the parasite detection using predictor variables. The p-values